Gestión de los ingresos y egresos del gobierno autónomo descentralizado parroquial de Febres Cordero De Febres Cordero, periodo 2021 – 2022. - Suarez Murillo, Sandy Jomara (2023)
The case study focuses on the management of income and expenses of the Rural Parochial Decentralized Autonomous Government of Febres Cordero during the period 2021-2022. The problem in this context lies in the decrease in traditional financing sources, such as contributions to parish councils, and the need to guarantee an efficient allocation of resources for local development. The organization of income reveals a worrying dependence on some sources, such as Central Government funds, which raises the importance of diversifying financing sources. In addition, a decrease is observed in unspecified income, such as VAT offsets and self-management, which require a detailed review. Regarding expenses, an investment in salaries and an increase in the fourteenth salary and expenses in office materials stand out. However, it is essential to evaluate whether these increases are aligned with local development objectives and are adequately justified. Current accounting and financial oversight procedures and practices are essential for the detection and prevention of irregularities. Adequate accounting records and periodic internal audits are observed. However, greater emphasis is needed on accounts receivable control and a rigorous review of unusual expenses.